A Simple Approach to Boost Capacitance: Flexible Supercapacitors Based on Manganese Oxides@MOFs via Chemically Induced In Situ Self‐Transformation. Issue 26 (4th May 2016) - Zhang, Yi‐Zhou; Cheng, Tao; Wang, Yang; Lai, Wen‐Yong; Pang, Huan; Huang, Wei
Abstract : An extremely simple in situ self‐transformation methodology is developed to introduce pseudocapacitance into the MOF system resulting in a largely boosted electrochemical performance: a three‐fold increase in capacitance as well as improved rate capacity. An all‐solid‐state hybrid flexible supercapacitor is fabricated based on the obtained MnO x –MHCF composite and activated carbon with an areal capacitance of 175 mF cm −2 at 0.5 mA cm −2 .